Keanekaragaman Ikan Invasif Di Perairan Umum Daratan Krueng Aceh - Yossa Liana; Faisal Syahputra; Suraiya Nazlia (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Aceh has a large potential for inland public water resources. One of the important inland waters is Krueng Aceh, Krueng Aceh is a river located in Aceh Province that originates at Cot Seukek, Aceh Besar District, passes through the city center (Peunayong) and empties into Lampulo, Banda Aceh City. The diversity of invasive fish in the inland waters of Krueng Aceh was carried out with the aim of identifying the types of invasive fish and to determine the diversity of invasive fish in the waters of Krueng Aceh as basic data in the management of inland common water resources. The research used a purposive sampling technique at sample points taken at 4 (four) points on the mainland of Krueng Aceh. Station 1 is located in Aneuk Galong Village, Station 2 is located in Bakoy Village, Station 3 is located in Pango Raya Village, Station 4 is located in Peunayong Village. The research results show that there are 9 types of fish in the public waters of the Krueng Aceh mainland which are dominated by baung fish. The station with the highest diversity results is station III located in Pango Raya which uses 4 types of fishing gear commonly used in the public waters of the Krueng Aceh mainland and gill net fishing gear is the most effective fishing gear used.